QUALITY MEASUREMENT OF TRANSPORTATION SERVICE APPLICATION GO-JEK USING ISO 25010 QUALITY MODEL - Izzatillah, Millati (Universitas Muria Kudus, 2019)
GO-JEK is the most widely used transportation service application by Indonesian society that its users reached 21.6% of the total users of transportation service application. GO-JEK application has 12 services include many functions that must running well. The services can be ordered by multiple users in the same time. Based on that condition, quality of GO-JEK application need to be measured that all functions running well or not. So, the result will be better application performance using mobile application quality measurement standards ISO 25010 Quality Model. Testing result of all subcharacteristics in ISO 25010 Quality Model, quality of GO-JEK application in Product Quality dimension is 79.30% on Android device and 80.88% on iOS device from maximum product quality value of mobile application is 91.37%. While in Quality in Use dimension is 76.22% from maximum quality in use value of mobile application is 94.75%. These things show GO-JEK application have a good quality in product quality dimension and in quality in use dimension or the user’s perspective.